2006
DOI: 10.1080/00207160500113173
|View full text |Cite
|
Sign up to set email alerts
|

On the maximal connected component of a hypercube with faulty vertices III

Abstract: Hypercube is one of the most popular topologies for connecting processors in multicomputer systems. In this paper we address the maximum order of a connected component in a faulty cube. The results established include several known conclusions as special cases. We conclude that the hypercube structure is resilient as it includes a large connected component in the presence of large number of faulty vertices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…One can even go further and ask what happens when more, even linearly many vertices are deleted. This was examined for the hypercube in [22] and for certain Cayley graphs generated by transpositions in [10], and it was shown that the resulting network will have a large component containing almost all vertices.…”
Section: Introductionmentioning
confidence: 99%
“…One can even go further and ask what happens when more, even linearly many vertices are deleted. This was examined for the hypercube in [22] and for certain Cayley graphs generated by transpositions in [10], and it was shown that the resulting network will have a large component containing almost all vertices.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25], it is possible to design efficient t/k diagnosis algorithm on hypercube in respect to k P 4. The method developed in this work should be extended to design t/k diagnosis algorithms on other types of interconnection networks such as star network [1], circulant network [2], folded hypercube [4], crossed cube [6], hierarchical cubic network [9], supercube [15] and twisted cube [19], to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [28][29][30] proved that the hypercube Q n with f faulty processors has a component of size at least 2 n − f − 1 if f ≤ 2n − 3, and size at least 2 n − f − 2 if f ≤ 3n − 6. Recently, Yang and Meng [27] determined the extra connectivity of hypercubes, Hsu et al [12] went further to establish the component connectivity of hypercubes.…”
Section: Fault Tolerance Of the Hhcmentioning
confidence: 99%
“…One can even go further and ask what happens when more vertices are deleted. This has been examined for the hypercube in [28][29][30] and for certain Cayley graphs generated by transpositions in [5], and it has been shown that the surviving network has a large component containing almost all vertices.…”
Section: Introductionmentioning
confidence: 98%